2011
DOI: 10.5897/ajb10.1661
|View full text |Cite
|
Sign up to set email alerts
|

Yield and storability of green fruits from hot pepper cultivars (Capsicum spp.)

Abstract: Five hot pepper (Capsicum spp.) cultivars were grown using randomized complete block design (RCBD) with three replications. Green peppers were stored under two storage conditions (ambient and evaporative cooling) with three replications. The plant growth characters yield and yield related traits were assessed. Melka Zala, PBC 600 and Mareko Fana had taller plants and had more number of branches. Melka Zala and Melka Dima were observed to be late and early maturing cultivar, respectively. The highest numbers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…In addition, Marecofana had the largest fruit size (7.3 g) while Melkashote had the least pod weight (4.5 g). The finding is in agreement with the result of Awole et al (2011) who reported wide range of pod size difference (6.6-17.0 gram) for five hot pepper varieties evaluated in Diredawa, Ethiopia.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, Marecofana had the largest fruit size (7.3 g) while Melkashote had the least pod weight (4.5 g). The finding is in agreement with the result of Awole et al (2011) who reported wide range of pod size difference (6.6-17.0 gram) for five hot pepper varieties evaluated in Diredawa, Ethiopia.…”
Section: Resultssupporting
confidence: 92%
“…Tesfaw et al (2013) also obtained significant fresh fruit yield difference (6.42 and 10.92 t ha -1 for Melkazala and Marecofana varieties) of hot pepper varieties evaluated in Bure, Northwestern Ethiopia. Moreover, Awole et al (2011) found a wide range of mean marketable yield variation (6.6-20.0 t ha -1 ) for five hot pepper varieties.…”
Section: Resultsmentioning
confidence: 91%
“…Growing and marketing of fresh produce in Ethiopia is complicated by high postharvest losses, which are about 30% (EARO, 2000;Workneh et al, 2011a, b, c). This high loss is due to packaging, storage facilities and poor means of transportation such as human labor, donkeys and mules, public transport and rented trucks (Kebede, 1991, Awole et al, 2011. Research result suggests that the selection and careful handling of perishable products determine the quality of fresh produce.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to remove heat in advance by cold storage which aims to reduce the rate of respiration, reduce susceptibility to microbes and reduce water content loss. Cooling methods that can be used is the method with water (hydrocooling), cooling using refrigeration orevaporative cooling (Awole et al, 2011;Rodoni et al, 2016). At this stage of the farmer according to Wigati et al (2019) postharvest losses may reach 2.33% due to improper handling.…”
Section: Results and Discussion Postharvest Handling Of Red Chili Farmersmentioning
confidence: 99%